RATTAN SPECIES AT THREE MOUNTS IN GUNUNG HALIMUN NATIONAL PARK, WEST JAVA - Titi Kalima (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2004)
Management of forest is believed that many basic knowledges about the nature of the forest is needed. One of them is to develop the forest as a resource of cane industry in a sustainable way. For this purpose, the composition, distribution and density of rattan species in Gunung Halimun National Park (INGH) were studied as a model. Data were collected from December 1994 until May 1995. For species composition on rattan in TNGH, three areas were observed namely in Mt. Kancana, Mt. Pameungpeuk and Mt. Pangkulahan using a continues belt transect method, from the elevation of 800-1,400 m above sea level. It was found that there were 13 species of rattans in the region. In terms of species richness and densities, Mt. Pameungpeuk comes first, followed by Mt. Pangku1ahan and Mt. Kancana. Calamus beteroides, C.javensis, Daemonorops melanocbaetes, and Plectocomia elongata are dominant both in seedling and nature forms. The nature rattans are relatively abundant in areas less than 1,000 meter above sea level and decrease in number of species as well as the minimal population in the higher altitude. Calamus ornatus grows well at 800-1,400 m asl, while Daemonorops ruber at 800-1,500 m asl, D.oblonga at 800-1,400 m asl.